Pengaruh CSR Terhadap Financial Performance pada Perusahaan Sub Sektor Makanan dan Minuman Tedaftar di BEI Tahun 2022-2023 - Hanifah Ihsani; Yuli Chomsatu Samrotun; Dimas Ilham Nur Rois (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research aims to test and analyze the influence of CSR on the financial performance of manufacturing companies listed on the BEI in 2022-2023. The population of this research is all food and beverage sub-sector manufacturing companies listed on the IDX. The sample selection in this study used purposive sampling with certain criteria so that 25 companies were obtained for 2 years of sample data for research. With 11 outlier data. So the sample data obtained is 39 data. The data used is secondary data obtained from financial reports. The data analysis technique uses simple linear regression analysis. The research results show that CSR has no effect on the financial performance of manufacturing companies in the food and beverage sub-sector in 2022-2023